Evolution of Covid-19 in Asia as of 08/30/2024 - Mora-Alvarado, Darner (2024)
This study completes the evolution of Covid-19 in Asia as of 08/30/2023 and closes the first investigation carried out on 12/03/2021, within the framework established by the National Water Laboratory, called “From the writings to the facts”, where real-time monitoring was provided to the Covid-19 pandemic-syndemic, supposedly originating in Wuhan, Hubei province, China. The results obtained indicate that the countries most affected by health in Asia were Russia and Yemen. And that this continent, despite the fact that it was the origin of the pandemic in China, was the third with the most health impact, behind America and Europe, which occupied first and second place in the Covid Health Impact Index. 08/19 to 08/30/2023.